The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1093/jac/dkq435
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Acinetobacter baylyi ADP1 to the biocide chlorhexidine leads to acquired resistance to the biocide itself and to oxidants

Abstract: Exposure of ADP1 to sublethal concentrations of chlorhexidine confers inducible resistance to lethal concentrations of chlorhexidine itself and to oxidants. An important link was demonstrated between exposure to a biocide and the gaining of resistance to both the biocide and oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Since several biocides have multiple, nonspecific mechanisms of action, similarly to tea tree oil, this same concern could apply to the oil. Although decreased antibiotic susceptibility following biocide exposure has been demonstrated in vitro (4,16), there is still debate as to what impact, if any, this has in clinical practice (17). The current study has demonstrated that tea tree oil has little impact on the development of antibiotic resistance, and that exposure to the major component terpinen-4-ol does not significantly alter antimicrobial susceptibility.…”
Section: Discussionmentioning
confidence: 61%
“…Since several biocides have multiple, nonspecific mechanisms of action, similarly to tea tree oil, this same concern could apply to the oil. Although decreased antibiotic susceptibility following biocide exposure has been demonstrated in vitro (4,16), there is still debate as to what impact, if any, this has in clinical practice (17). The current study has demonstrated that tea tree oil has little impact on the development of antibiotic resistance, and that exposure to the major component terpinen-4-ol does not significantly alter antimicrobial susceptibility.…”
Section: Discussionmentioning
confidence: 61%
“…The mechanism of chlorhexidine resistance in A. baumannii is purportedly associated with bacterial efflux pumps. 10 In this study, although the magnitude of chlorhexidine exposure resulting in the increase in A. baumannii chlorhexidine MICs 50/90 during the 12-month advanced source control period, it did not achieve the threshold for the emergence of chlorhexidine-resistant XDR A. baumannii detection, yet our data suggest that ongoing active surveillance for chlorhexidineresistant A. baumannii as well as its MIC 50/90 is needed to evaluate the emergence of chlorhexidine-resistant A. baumannii.…”
Section: Increase In Chlorhexidine Minimal Inhibitory Concentration Omentioning
confidence: 54%
“…AceI belongs to the bacterial transmembrane pair family and is grouped as a prototype member of the proteobacterial chlorhexidine efflux family (563). Similarly, the exposure of Acinetobacter baylyi to chlorhexidine also induced resistance to chlorhexidine and oxidants (564), which could potentially be attributed to efflux pumps.…”
Section: Acinetobacter Sppmentioning
confidence: 99%